The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/lang.12224
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Use in Language Learning: A Meta‐Analysis

Abstract: This study applied systematic meta‐analytic procedures to summarize findings from experimental and quasi‐experimental investigations into the effectiveness of using the tools and techniques of corpus linguistics for second language learning or use, here referred to as data‐driven learning (DDL). Analysis of 64 separate studies representing 88 unique samples reporting sufficient data indicated that DDL approaches result in large overall effects for both control/experimental group comparisons (d = 0.95) and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
187
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(238 citation statements)
references
References 57 publications
4
187
2
6
Order By: Relevance
“…Data‐driven learning refers to direct applications of corpora in which learners themselves acquire hands‐on experience of using a corpus for learning purposes, often with guided tasks or materials (see Mizumoto & Chujo, , for different types of data‐driven learning). Its overall effectiveness (i.e., resulting in positive outcomes) for language learning has been reported in meta‐analyses (Boulton & Cobb, ; Mizumoto & Chujo, ). In L2 academic writing studies, corpus consultation as a reference source has been found effective, among other reported benefits (Yoon, ), in correcting writing errors (Gaskell & Cobb, ) and raising awareness about the writing conventions of a specific discourse community (Chang, ; Friginal, ), particularly by using a specialized research article corpus (Lee & Swales, ).…”
Section: Rationale For Developing a Support Tool For Research Articlementioning
confidence: 95%
“…Data‐driven learning refers to direct applications of corpora in which learners themselves acquire hands‐on experience of using a corpus for learning purposes, often with guided tasks or materials (see Mizumoto & Chujo, , for different types of data‐driven learning). Its overall effectiveness (i.e., resulting in positive outcomes) for language learning has been reported in meta‐analyses (Boulton & Cobb, ; Mizumoto & Chujo, ). In L2 academic writing studies, corpus consultation as a reference source has been found effective, among other reported benefits (Yoon, ), in correcting writing errors (Gaskell & Cobb, ) and raising awareness about the writing conventions of a specific discourse community (Chang, ; Friginal, ), particularly by using a specialized research article corpus (Lee & Swales, ).…”
Section: Rationale For Developing a Support Tool For Research Articlementioning
confidence: 95%
“…Nowadays, better software is available. Boulton and Cobb (, p. 382) argued that they did not use meta‐regression because that would “mainly [be] suited to continuous [predictor variables].” However, categorical predictors can easily be included in a regression model through dummy coding or other forms of contrast coding. After all, an analysis of variance model is also a regression model with categorical predictors (Field, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The only difference is that, as in metaanalysis, the dependent variable is not the measurement originally used in the Goldschneider &DeKeyser, 2001, andLi, 2010). Instead, researchers often study predictor variables by splitting their data set by the levels of their predictor(s) and calculating separate effect sizes for all these subsets (e.g., Boulton & Cobb, 2017;Mackey & Goo, 2007;Montero Perez et al, 2013). Significance can be determined by considering whether the confidence intervals of the effect sizes of the subsets overlap (Mackey & Goo, 2007) or through Q tests (Montero Perez et al, 2013).…”
Section: Meta-analysis and Meta-regression In L2 Researchmentioning
confidence: 99%
“…For our analysis, we used the corpus profiling program AntConc to make word lists based on frequency, and to measure coverage for OBEL and Baumann and Culligan's (1995) version of West's (1953, see www.lextutor.ca/freq/lists_ download) General Service List (GSL). To estimate coverage, we created word lists that exclude OBEL and GSL word families from the SEW texts.…”
Section: Creating the Sew Corpusmentioning
confidence: 99%